FEATURES OF CONDUCTING THE INVESTIGATION OF ACCIDENTS AND OTHER DAMAGES TO THE HEALTH OF WORKERS AT THE PRODUCTION - Shadieva Karina Isamiddinovna; Khamidullaev Fathulla Faizullaevich (European Journal of Life Safety and Stability (2660-9630), 2021)
Fulfilling the requirements of the Law of the Republic of Uzbekistan "On labor protection" in the Republic, special attention is paid to the issues of creating healthy and safe working conditions for workers, reducing the impact on them of hazardous and harmful production factors. However, industrial injuries do occur. High-quality and timely investigation of accidents or other injuries to the health of workers at work is of great importance for both the enterprise and the victim. Only objectively established circumstances make it possible to determine the true causes of the accident, develop and implement preventive measures, determine the perpetrators and the degree of their responsibility, perform an analysis of injuries and establish social protection measures for the victim. By the Resolution of the Cabinet of Ministers of the Republic of Uzbekistan No. 286 dated 06.06.97. approved and put into effect "Regulations on the investigation and accounting of accidents at work and other injuries to the health of workers associated with the performance of their work duties."